AL-QUR’AN DAN KEBENARAN ILMIAH: JALINAN EPISTEMOLOGI - Muhammad Patri Arifin (Al-Munir: Jurnal Studi Ilmu Al-Qur'an dan Tafsir, 2024)
This paper compares Islamic epistemology with Western thought in the context of the origin, nature, and types of knowledge. The fundamental difference lies in their understanding of the reality of knowable objects. Islamic epistemology recognizes the entire universe as an object of knowledge and acknowledges Allah as its Creator, whereas Western thought tends to limit knowledge to observation and empirical methods. Scientific truth in Western thought is generally established through the scientific method and various theories of truth. Furthermore, this paper highlights the role of the Qur’an as a source of knowledge that validates and integrates other sources of knowledge, including empiricism, rationalism, intuition, and revelation, while emphasizing the respective domains in which each operates. The Qur’an is viewed as a comprehensive guide that provides the foundational principles of knowledge, while the development and advancement of scientific understanding remain the responsibility of human beings. In this regard, numerous scientific truths mentioned in the Qur’an have been confirmed through scientific discoveries and research conducted by scholars and scientists. Therefore, this study demonstrates the close relationship between Islamic epistemology and the Qur’an, showing how the Qur’an serves as a fundamental framework for understanding knowledge and truth while accommodating various legitimate sources of human understanding.